PENENTUAN KADAR 8-HIDROKSI-2’-DEOKSIGUANOSIN (8-OHdG) DALAM URIN TIKUS SETELAH TERPAPAR ETANOL DAN ASAP ROKOK - Iflahah, Mahardika Aprilia; Suaniti, Ni Made; Raka Astiti Asih, Ida Ayu (Jurnal Kimia (Journal of Chemistry), 2014)
Urinary level of 8-OHdG in rats after exposure to ethanol and smoke have been investigated for 15 days with TLC-Spectrophotodensitometer. Ethanol and smoke exposure to could increase the number of Reactive Oxygen Species (ROS), which could lead to a state called oxidative stress. 8-OHdG compound is the result of DNA oxidation by ROS in the body in the form of guanine nucleotide. This 8-OHdG is a water-soluble compound excreted in urine easily. In this study, exposure of ethanol and smoke both singly and combined had an effect on the level of 8-OHdG. Urinary level of 8-OHdG in the control group; groups exposed to ethanol, smoke, and ethanol-smoke were (0,00 ± 0,00)%, (0,33 ± 0,08)%, (0,25 ± 0,10)%, and (0,57 ± 0,27)% respectively.
Keywords: Ethanol, Smoke, ROS, 8-OHdG, TLC-Spectrophotodensitometer